Navigating the anarchival landscape of Philippine cinema insights from Bliss Cua Lim’s Archival afterlives of Philippine Cinema - Mendizabal, Adrian D. (2024)
Access online through this link:http://plarideljournal.org/article/navigating-the-anarchival-landscape-of-philippine-cinema-insights-from-bliss-cua-lims-archival-afterlives-of-philippine-cinema
Keywords: Lim, Bliss Cua; Film archives; Audiovisual archives